Peaceful coexistence? The role of religious schools and NGOs in the growth of female secondary schooling in Bangladesh - Niaz Asadullah; Nazmul Chaudhury (Institute for the Study of Labor (IZA), 2012)
BRAC, a non-governmental organization (NGO), runs a large number of non-formal primary schools in Bangladesh which target out-of-school children from poor families. These schools are well-known for their effectiveness in closing gender gap in primary school enrolment. On the other hand, registered non-government secondary madrasas (or Islamic schools) today enrol one girl against every boy student. In this paper, we document a positive spillover effect of BRAC schools on female secondary enrolment in registered madrasas. Drawing upon school enrolment data aggregated at the region level, we first show that regions that had more registered madrasas experienced greater secondary female enrolment growth during 1999-2003, holding the number of secular secondary schools constant. In this context we test the impact of BRAC-run primary schools on female enrolment in registered madrasas. We deal with the potential endogeneity of placement of BRAC schools using instrumental variable approach. Controlling for factors such as local-level poverty, road access and distance from major cities, we show that regions with a greater presence of BRAC schools have higher female enrolment growth in secondary madrasas. The effect is much bigger when compared to that on secondary schools.
Keywords: I21; Z12; O12; O15; 330; externalities; NGO schools; madrasas; female schooling; Frauenbildung; Allgemeinbildende Schule; Nichtregierungsorganisation; Religion; Externer Effekt; Bangladesch